The Effects of Melatonin on Ethylene Glycol-induced Nephrolithiasis: Role on Osteopontin mRNA Gene Expression - ŞENER, GÖKSEL; ÇETİNEL, ŞULE; ŞENER, TARIK EMRE; TANIDIR, YILÖREN (ELSEVIER SCIENCE INC, 2017)
OBJECTIVE To evaluate the protective effects of melatonin (Mel) on an ethylene glycol (EG)-induced nephrolithiasis model in rats. MATERIALS AND METHODS Thirty-two Wistar albino rats were divided into 4 groups: control, EG, prevention Mel (Mel + EG + Mel), and therapeutic Mel (EG + Mel). EG (0.75%) was added to drinking water to create nephrolithiasis model. The EG group received EG and the Mel + EG + Mel group received both EG and Mel for 8 weeks. In the EG + Mel group, EG is given for 8 weeks and Mel is given for the last 4 weeks of the experiment. At the end of experimental period, urine, blood samples, and tissues were collected. RESULTS In 24-hour urine samples, calcium, citrate, and creatinine levels were decreased and oxalate levels were increased in the EG group, whereas Mel prevention and Mel treatment reversed these parameters back to control levels. Malondialdehyde, glutathione activities, myeloperoxidase, superoxide dismutase levels, and caspase-3 activity showed improvements in the Mel-treated groups when compared with the EG group. 8-Hydroxydeoxyguanosine, matrix metalloproteinase 9 levels, N-acetyl-beta-glucosaminidase activity, and osteopontin mRNA expression were elevated in the EG group and decreased back to control levels in the Mel + EG + Mel and EG + Mel groups. Histological examination showed improvement in the Mel-treated groups when compared with the EG group. CONCLUSION Mel can prevent crystalluria and kidney damage due to crystal formation and aggregation. It can be considered as a potential prophylactic and protective agent in high-risk patients with urinary stone formation or recurrence if supported by further clinical studies. (C) 2016 Elsevier Inc.
Keywords: RENAL EPITHELIAL-CELLS; LIPID-PEROXIDATION; OXIDATIVE STRESS; STONE DISEASE; OXALATE; KIDNEY; MYELOPEROXIDASE; ANTIOXIDANTS; PATHOGENESIS; INJURY